The Environmental Utilization as a Learning Resource for Civic Education in Elementary Schools by Prospective Teacher College Students - Wuri Wuryandani; Fathurrohman Fathurrohman; Herwin Herwin (Jurnal Prima Edukasia, 2022)
Civic education is one of the compulsory subjects in elementary schools. This subject has a strong relationship with the social environment. This study aims to identify various types of environmental learning resources used by prospective teacher students in designing learning tools for civic education in elementary schools. Furthermore, the type of this research is descriptive research with a qualitative approach. The subjects of this study were college students of the elementary school teacher education study program who took the civic education development course. The data collection in this study was carried out by observations, interviews, and document analysis. The validity of the data was checked using triangulation. The analysis used in this study is inductive. Finally, the results showed that the environmental utilization by prospective teacher college students in the learning of civic education in elementary schools involves the family environment, school environment, and community environment. In addition, the use of the environment as a learning resource is intended to develop teaching materials and to prepare LKPD activities.